25OH vitamin D3 in biliary atresia: a simple and under-utilised diagnostic method - Song, Fangjuan; Li, Wanfu; Chen, Zhida; Maimaijiang, Ayiguzali; Wang, Yaqi (Frontiers in Pediatrics, 2025)
BackgroundBiliary atresia is a form of pediatric cholangiopathy that affects the bile ducts of the liver. If left undiagnosed and untreated, it often leads to liver failure and death within 1–2 years of age. The treatment approach for this condition is recognized as the Kasai surgical procedure,which has been shown to achieve optimal outcomes when performed within 60 days of age. Furthermore, the timing of surgery has been identified as a crucial factor in determining patient prognosis. The current clinical practice involves the use of ultrasound as a primary diagnostic tool. Serum γ-glutamyltranspeptidase and other biochemical indicators are utilized in the diagnosis of biliary atresia, yet challenges persist regarding the occurrence of false-positive results. Consequently, there is an urgent clinical necessity to investigate non-invasive indicators for the early diagnosis of BA in children, with the objective of enhancing the accuracy of early diagnoses. In clinical practice, we frequently encounter cases of severe vitamin D deficiency in children diagnosed with BA. In recent years, the association between vitamin D and liver fibrosis in chronic liver disease has been substantiated. The objective of this study was to ascertain the clinical value and significance of 25(OH)D3 in the early diagnosis of BA.ObjectiveThe best early diagnosis of BA is currently clinically inconclusive, and no test can confirm the diagnosis before surgery. To explore the clinical value of 25(OH)D3 in the diagnosis of biliary atresia (BA).MethodsThe observation group comprised paediatric patients with biliary atresia admitted to the First Affiliated Hospital of Xinjiang Medical University between January 2024 and March 2025. The control group consisted of paediatric patients with cholestatic diseases caused by conditions other than biliary atresia during the same period.ResultsThere were significant differences in ultrasound results, serum γ-glutamyl transpeptidase level and 25(OH)D3 level between the BA group and the non-BA group (P < 0.05). The level of γ-glutamyl transpeptidase in the BA group was significantly higher than that in the non-BA group (P < 0.05), the level of direct bilirubin in the BA group was significantly higher than that in the non-BA group (P < 0.05), and the level of 25(OH)D3 in the BA group was significantly lower than that in the non-BA group (P < 0.05). A 25(OH)D3 cut-off level of 20.59 or lower combined with ultrasound results, or a 25(OH)D3 cut-off level of 20.59 or lower, ultrasound results, and serum γ-glutamyl transpeptidase cut-off levels of 283.89 or higher were combined to increase the sensitivity by 2.5%, specificity by 1.96%, PPV by 2.5%, NPV by 1.96%, and accuracy by 2.20% compared with 25(OH)D3 alone.ConclusionsThe level of 25(OH)D3 can be used as a new force for diagnosing BA to provide an important detection basis for whether children need early surgical treatment, and is a good indicator for the diagnosis and differential diagnosis of BA.Moreover, the combined ultrasound results or 25(OH)D3 level, serum γ-glutamyl transpeptidase, and ultrasound results have higher diagnostic efficiency, and it is recommended to combine them for diagnosis.